Studi Peningkatan Daya Tarik Kawasan Wisata Situs Goa Mandu Tontonan Kabupaten Enrekang - Muh Fikri Anwar; Batara Surya; Jufriadi Jufriadi; Nurul Ulfa Haerani (Journal of Urban Planning Studies, 2023)
In this study the aims were to find out the opportunities and challenges in increasing attractiveness in the Goa Mandu Tontonan Tourism Site area in Enrekang Regency and to find out how to increase attractiveness in the Goa Mandu Tontonan Tourism Site area in Enrekang Regency.The research method used in this study is a descriptive research method using a qualitative approach. To answer the strategy in increasing the attractiveness of the Goa Mandu Tontonan Tourism Site area, Enrekang Regency uses a SWOT analysis, Opportunities and challenges in the development of Goa Mandu Tontonan Tourism Sites, such as facilities, promotions, and other factors that still need serious handling to make it more attractive to tourists and become a source of economic income for the community and carry out promotions to advance the attractiveness of the Goa Mandu Tontonan Site Tourism Area in the future to increase the number of tourist visits to the tourist area of ​​the Tontonan Goa Mandu site